2013
DOI: 10.1111/jgh.12191
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and systemic hemodynamic derangements predict early mortality and recovery in patients with acute‐on‐chronic liver failure

Abstract: Baseline HVPG is an independent predictor of mortality in ACLF patients. The portal and systemic circulatory anomalies regress substantially by 90 days and correlate with clinical recovery. However, in the initial phase, the raised portal pressure predisposes these patients to high risk of variceal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…The mean HVPG in our cirrhotic cohort was 15.8 ± 6.2 mmHg. This is similar to the studies published by Kim et al (10) and Garg et al, (11) which reported a mean HVPG of 15.6 ± 5.1 mmHg and median HVPG of 16 (range 12-30) mmHg, respectively. Despite a small sample size, our study demonstrated a significant difference (p = 0.04) in the risk of variceal bleeding in cirrhotics with a HVPG ≥ 12 mmHg compared with those with a HVPG < 12 mmHg.…”
Section: Discussionsupporting
confidence: 81%
“…The mean HVPG in our cirrhotic cohort was 15.8 ± 6.2 mmHg. This is similar to the studies published by Kim et al (10) and Garg et al, (11) which reported a mean HVPG of 15.6 ± 5.1 mmHg and median HVPG of 16 (range 12-30) mmHg, respectively. Despite a small sample size, our study demonstrated a significant difference (p = 0.04) in the risk of variceal bleeding in cirrhotics with a HVPG ≥ 12 mmHg compared with those with a HVPG < 12 mmHg.…”
Section: Discussionsupporting
confidence: 81%
“…The fact that the prevalence of extrahepatic organ failure is not higher in the extrahepatic insult group emphasizes that the final common pathway of deterioration and mortality in ACLF is systemic inflammation and subsequent circulatory dysfunction resulting in multiorgan failure 19,20 irrespective of the cause of acute insult. In our previous study, we reported increasing inhospital mortality with increasing numbers of organ failures (26% with single organ failure and 58%, 71%, and 100% with two, three, and four organ failures, respectively) in ACLF.…”
Section: Discussionmentioning
confidence: 95%
“…6 Furthermore, the CANONIC study was conducted in a European population, and there have been only a few published studies on the outcome of ACLF in an Asian population to date. 13,14 In the present study, hospitalized patients with active alcoholism and severe form of alcoholic liver disease who developed ACLF more frequently had an infection and SIRS and higher MELD, MELD-Na, and severity scores for alcoholic liver disease such as MDF and ABIC.…”
Section: Discussionmentioning
confidence: 96%